Agroecological Transition in the Cotton Zone: Analysis of Technical-Economic and Environmental Performances in Northern Benin - A Literature Review - Abdou Ganiou Abou Chabi; Silvère Tovignan; Jacob Afouda Yabi (European Scientific Journal, ESJ, 2023)
This article is a systematic review of the knowledge of technical-economic and environmental performance in agroecological transition. The data collected in the Scopus and dimension database concerned exclusively published articles and journals, using the relevant terms. Thus, 227 documents exported from Scopus and dimension were submitted to a bibliometric analysis with the Citespace software, then the inclusion and exclusion criteria were carried out according to the ROSES standards.  The results reveal that the annual production of studies related to the technical-economic and environmental performance in agro-ecological transition is increasing with an annual growth rate of about 1.3%.  There is a common understanding of agroecological transition. The agroecological transition addresses the problems of the food system from field to plate, covering all activities and actors involved in the cultivation based on natural resources. Among the agroecological practices analyzed, the application of compost seems the most promising to be scaled up to improve economic and environmental performance.